2020
DOI: 10.1002/advs.202000709
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Phenotypic Divergence in Wild Barley Driven by Microgeographic Adaptation

Abstract: Microgeographic adaptation is a fundamental driving force of evolution, but the underlying causes remain undetermined. Here, the phenotypic, genomic and transcriptomic variations of two wild barley populations collected from sharply divergent and adjacent micro-geographic sites to identify candidate genes associated with edaphic local adaptation are investigated. Common garden and reciprocal transplant studies show that large phenotypic differentiation and local adaptation to soils occur between these populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…[ 18 ] and Bian et al. [ 3 ] revealed that genomic divergence plays a crucial role in edaphic adaptation of wild barley. Both studies identified novel genes and alleles associated with ABA signaling and root architecture, which facilitates the wild barley to adapt to the dry Terra Rossa and Chalk soils.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 18 ] and Bian et al. [ 3 ] revealed that genomic divergence plays a crucial role in edaphic adaptation of wild barley. Both studies identified novel genes and alleles associated with ABA signaling and root architecture, which facilitates the wild barley to adapt to the dry Terra Rossa and Chalk soils.…”
Section: Discussionmentioning
confidence: 99%
“…The studies on evolutionary microsites in Israel provided excellent examples of the adaptation to micro ecological environment from viruses and bacteria, through fungi, plants, and animals. [38][39][40][41][42][43][44] Recently, Wang et al [18] and Bian et al [3] revealed that genomic divergence plays a crucial role in edaphic adaptation of wild barley. Both studies identified novel genes and alleles associated with ABA signaling and root architecture, which facilitates the wild barley to adapt to the dry Terra Rossa and Chalk soils.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ca 2+ is the most abundant element in the chalk soil ( Figure 1 D), followed by Si 4+ , Al 3+ , Fe 3+ , and Mg 2+ , and Si 4+ is the most abundant chemical in the abutting contrasting basalt soil, followed by Al 3+ , Fe 3+ , and Ca 2+ . Al 3+ , Fe 3+ , and Ca 2+ contents are significantly different between the two soils [ 35 ]. Thus, basalt is generally acidic, while chalk is slightly alkaline [ 36 ].…”
Section: Introductionmentioning
confidence: 99%